2015
DOI: 10.1016/j.jare.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Possible drug–drug interaction in dogs and cats resulted from alteration in drug metabolism: A mini review

Abstract: Graphical abstractEffects of ketoconazole treatment on intravenous pharmacokinetics of midazolam (CYP3A substrate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…2 Drug interactions and adverse reactions have been reported in association with both topical and systemic usage of azoles. 8,9 Furthermore, there are concerns regarding the evolution of Malassezia drug resistance. Some in vitro studies have reported that Malassezia from lesions in dogs with atopic dermatitis were less susceptible to, or even resistant to, azole antifungals as compared to Malassezia taken from clinically asymptomatic dogs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Drug interactions and adverse reactions have been reported in association with both topical and systemic usage of azoles. 8,9 Furthermore, there are concerns regarding the evolution of Malassezia drug resistance. Some in vitro studies have reported that Malassezia from lesions in dogs with atopic dermatitis were less susceptible to, or even resistant to, azole antifungals as compared to Malassezia taken from clinically asymptomatic dogs.…”
Section: Discussionmentioning
confidence: 99%
“…At outset (Day 0), Lesion Scores were very similar for placebo-versus Aptus â -treated paws [median (range): 10 (6-15) and 10 (6-15) respectively]. By end date, Lesion Scores were reduced in both placebo-and Aptus â -treated paws [8 (3-13) and 7.5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), respectively]. Examining the absolute differences between paired paws, Aptus â succeeded in reducing Lesion Scores relative to placebo by a mean difference of 1.3 points (95% confidence interval 0.1-2.6), which was statistically significant (Wilcoxon signed rank P = 0.041).…”
Section: Lesion Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Enrofloxacin, a fluoroquinolone, has been reported to interact with the pharmacokinetics of other drugs such as the methylxanthine theophylline (Intorre, Mengozzi, Maccheroni, Bertini, & Soldani, 1995) and NSAIDs on several occasions (Abo- -Sooud & Al-Anati, 2011;Ogino, Mizuno, Ogata, & Takahashi, 2005;Rahal, Kumar, Ahmad, & Malik, 2008). The reason for the interaction of enrofloxacin with the pharmacokinetics of certain drugs is thought to be linked to the inhibition of particular drug metabolizing cytochrome P450 (CYP) enzymes, such as CYP1A1 and CYP1A2 (Intorre et al, 1995;Rahal et al, 2008;Regmi, Abd El-Aty, Kuroha, Nakamura, & Shimoda, 2005;Sasaki & Shimoda, 2015;Vancutsem & Babish, 1996). While enrofloxacin seems to increase the half-life of elimination of theophylline, the effect on the metabolism of NSAIDs seems to be less consistent (Intorre et al, 1995).…”
Section: Pharmacodynamic Analysismentioning
confidence: 99%
“…Interestingly, these two databases have different features [12] and show different results in identifying potential DDIs between the prescribed drugs for oral cancer treatment [13]. Also, in veterinary medicine as well as human medicine, multidrug therapy is commonly used for the treatment of animals [14]. However, few studies focus on the competency of databases to detect potential DDIs for the management of complicated diseases in animals, for example, cardiovascular diseases, urinary diseases, metabolic diseases, skin diseases and cancers.…”
Section: Introductionmentioning
confidence: 99%